The Feasibility of performing resistance exercise with acutely ill hospitalized older adults - Mallery, Laurie H (BioMed Central, 2003)
BACKGROUND: For older adults, hospitalization frequently results in deterioration of mobility and function. Nevertheless, there are little data about how older adults exercise in the hospital and definitive studies are not yet available to determine what type of physical activity will prevent hospital related decline. Strengthening exercise may prevent deconditioning and Pilates exercise, which focuses on proper body mechanics and posture, may promote safety. METHODS: A hospital-based resistance exercise program, which incorporates principles of resistance training and Pilates exercise, was developed and administered to intervention subjects to determine whether acutely-ill older patients can perform resistance exercise while in the hospital. Exercises were designed to be reproducible and easily performed in bed. The primary outcome measures were adherence and participation. RESULTS: Thirty-nine ill patients, recently admitted to an acute care hospital, who were over age 70 [mean age of 82.0 (SD= 7.3)] and ambulatory prior to admission, were randomized to the resistance exercise group (19) or passive range of motion (ROM) group (20). For the resistance exercise group, participation was 71% (p = 0.004) and adherence was 63% (p = 0.020). Participation and adherence for ROM exercises was 96% and 95%, respectively. CONCLUSION: Using a standardized and simple exercise regimen, selected, ill, older adults in the hospital are able to comply with resistance exercise. Further studies are needed to determine if resistance exercise can prevent or treat hospital-related deterioration in mobility and function.